TINDAK TUTUR ILOKUSI DALAM FILM "YUNI" KARYA KAMILA ANDINI - Munggarani, Neni; Syahrani, Agus; Jupitasari, Mellisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The background of this research is done because when dialogue between figures in the film, there is a delivery of messages or intentions of speakers to speakers. The purpose of this study is to know and describe the type and function of the illocusion speech in the Yuni film. The method used in this study is a descriptive method with a qualitative form of research. The source of the data in this study is the Yuni film by Kamila Andini. The data in this study is the illocumental speech in the Yuni film by Kamila Andini. The data collection technique performed in the study is documentation study. The data collector used in this study is a visual audio document in the form of films to collect data and use indicators of the type and function of illocusion speech to classify the speech. The instruments used in this study are the classification of the type and function of illocusion speech. The illocusion speech in the Yuni film totaled 43 data with details of 7 representative speakings, 24 directive speakings, 9 expressive speakings, 3 commissive speakings, 43 data are divided into 17 functions. As well as from this analysis can be implemented in Indonesian learning at the level of High Schools of criticism and essay text material